1999
DOI: 10.1002/(sici)1097-0215(19990719)82:2<282::aid-ijc20>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Establishment, characterisation and partial cytokine expression profile of a new human osteosarcoma cell line (CAL 72)

Abstract: Permanent human osteosarcoma cell lines are important tools for the study of bone cancer. As representative of an osteoblastic phenotype, they partly reflect their normal osteoblastic counterparts and, thus, may represent appropriate models to investigate the mechanisms involved in bone remodelling and in haematopoietic differentiation. In the present work, we describe a new human cell line, CAL 72, obtained from an osteosarcoma of the knee of a 10‐year‐old boy. These cells grow in continuous culture, and kary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 13 publications
4
39
0
Order By: Relevance
“…Notably, statins increased caspase-3 like activity in CAL-72 cells that are resistant to various chemotherapies. 22 We also found that lipophilic statins increased caspase-9 activity at an early time point (15 h), whereas caspase-8 activity or Fas/FasL expression were not significantly changed (data not shown), indicating that statins activated caspase-9 upstream of caspase-3 in these osteosarcoma cells. To confirm that statins activate caspases in SaOS 2 and OHS 4 human osteosarcoma cells, the cells were pretreated for 1 h with z-Val-Ala-Asp-fluoromethylketone (zVAD-fmk), a broad spectrum caspases inhibitor which blocks apoptotic cell death induction but not necrotic cell death.…”
Section: Lipophilic Statins Induce Caspases-dependent Apoptosis In Humentioning
confidence: 74%
See 1 more Smart Citation
“…Notably, statins increased caspase-3 like activity in CAL-72 cells that are resistant to various chemotherapies. 22 We also found that lipophilic statins increased caspase-9 activity at an early time point (15 h), whereas caspase-8 activity or Fas/FasL expression were not significantly changed (data not shown), indicating that statins activated caspase-9 upstream of caspase-3 in these osteosarcoma cells. To confirm that statins activate caspases in SaOS 2 and OHS 4 human osteosarcoma cells, the cells were pretreated for 1 h with z-Val-Ala-Asp-fluoromethylketone (zVAD-fmk), a broad spectrum caspases inhibitor which blocks apoptotic cell death induction but not necrotic cell death.…”
Section: Lipophilic Statins Induce Caspases-dependent Apoptosis In Humentioning
confidence: 74%
“…CAL-72 cells display chromosomal abnormalities and a distinct cytokine expression profile compared to MG63 and SaOS 2 cells. 22 All cells were cultured in Dulbecco's-modified Eagle medium (Invitrogen Corporation, Paisley, Scotland) in the presence of 10% heat inactivated fetal calf serum (FCS), 1% L-glutamine and penicillin/streptomycin (10 000 U/ml and 10 000 mg/ml, respectively) with medium change every 2-3 days. Importantly, all the experiments described below were performed in cells cultured in serum supporting conditions, i.e., in the presence of 10% FCS.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Glassbottomed culture dishes were coated with collagen type I to mimic hard collagenous bone. The osteosarcoma cell line CAL-72, which is widely used as a model for osteoblasts (Rochet et al, 1999), was seeded on top of it and grown to confluence to mimic the bone-lining osteoblasts. In the publication by Katayama and co-workers (Katayama et al, 2006) G-CSF was used to induce mobilization.…”
Section: Highly Simplified In Vitro Model Of the Endosteal Nichementioning
confidence: 99%
“…MG-63 was obtained from Dr Clemens-Lowik (Leiden University Medical Center); MNNG-HOS and SaOs-2, courtesy of Dr F van Valen (Westfa¨lische Wilhelms-Universitat Mu¨nster) and CAL-72 courtesy of Dr J Gioanni (Laboratoire de Cancerologie, Faculte de Medicine, Nice), as described previously. 18,19 Human glioma cell lines were used including VU1.2 (obtained from a glioma patient, VU-University Amsterdam), U118, U373 and IGRG-121 (all CAR negative, except U373) as described before. 20,21 For CAR upregulation studies, either 5-aza-2 0 -deoxycytidine (5-aza-2-CdR) (Sigma, St Louis, MO), trichostatin A (TSA) (Sigma) or sodium phenylbutyrate (NaPheBt) (Triple Crown America, Inc., Perkasie, PA) were added to the growth medium.…”
Section: Cell Lines and Tissue Samplesmentioning
confidence: 99%